A thick negative electrode and its preparation method and application

The combination of dispersants and binder compositions in thick electrodes addresses electrolyte wettability and lithium ion migration issues, improving the flexibility and adhesion of the electrode, resulting in enhanced battery performance and cycle stability.

CN115347192BActive Publication Date: 2024-12-31EVE POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211166590.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-21
Publication Date
2024-12-31
Estimated Expiration
2042-09-21

AI Technical Summary

Technical Problem

Thick electrodes in lithium-ion batteries face issues with poor electrolyte wettability, long lithium ion migration paths, large concentration polarization, and poor cycle and storage performance, which affect conductivity and overall battery performance.

Method used

A thick negative electrode is developed using a combination of a dispersant and different types of binder compositions, including a block copolymer binder with polyacrylate segments and emulsion-type binders, to enhance adhesion and flexibility, forming a stable three-dimensional network structure and maintaining electronic paths for improved kinetic properties and cycle performance.

Benefits of technology

The solution improves the flexibility and adhesion of the electrode, reducing active material fall-off and enhancing battery performance, with capacity retention rates over 90% after 3000 cycles and good low-temperature discharge performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115347192B_ABST
    Figure CN115347192B_ABST
Patent Text Reader

Abstract

The present invention provides a negative thick electrode and a preparation method and application thereof, wherein the negative thick electrode comprises a current collector and a negative active material layer disposed on the surface of the current collector, wherein the negative active material layer comprises a negative active material, a conductive agent, a dispersant and a combined binder, wherein the combined binder comprises a binder A and a binder B, wherein the binder A comprises a block copolymer, wherein the middle of the block copolymer is a polyacrylate segment, and both ends comprise a polyacrylic acid segment and a polyvinyl alcohol segment, wherein the binder B comprises an emulsion-type binder, and the negative electrode sheet of the present invention comprises both the binder A and the binder B, and the electrode sheet comprising the binder A alone is hard and brittle, and has excellent dynamic performance. The simultaneous use of the binder A and the binder B makes the negative electrode sheet have good flexibility, is conducive to processing, reduces the situation where the active material falls off from the sheet, and reduces the risk of short circuit of the electrochemical energy storage device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a thick negative electrode and a preparation method and application thereof. Background Art

[0002] In recent years, the new energy industry has developed rapidly, and the demand for lithium-ion batteries has grown rapidly. The market has put forward higher requirements for the energy density, low temperature performance, fast charging performance, safety, and cost of lithium-ion batteries. Improving battery performance has become a key research area for various material manufacturers and battery manufacturers. Lithium-ion batteries are now widely used in new energy vehicles, energy storage batteries, consumer batteries and other fields. With the promotion and development of new energy vehicles and energy storage, energy density and cost have become the focus of researchers; batteries prepared with conventional thickness pole pieces are difficult to meet the requirements, and the design of thick electrodes can achieve the same area of ​​current collectors carrying more electrode active materials, which can increase energy density and reduce costs. Thick electrodes face the problem of conductivity, which affects the performance of batteries.

[0003] CN113285062A discloses a thick electrode material and a preparation method thereof, and a lithium ion battery, comprising: adding a conductive agent, a thickener, a binder and a solvent to an electrode active material with a small particle size to prepare a first electrode slurry; adding a conductive agent, a thickener, a binder and a solvent to an electrode active material with a large particle size to prepare a second electrode slurry; conveying the first electrode slurry and the second electrode slurry to the respective corresponding die heads of a double-die coater through two sets of slurry transportation systems respectively for simultaneous intermittent coating an even number of times, and keeping the first electrode slurry above the second electrode slurry or the second electrode slurry above the first electrode slurry during each coating, and after drying and rolling treatment, the thick electrode is obtained.

[0004] CN112151743A discloses a pore-forming method for a thick electrode and its product and use. The pore-forming method comprises applying a slurry with a viscosity of 6000m-9000mPa·s on the surface of a current collector with a surface roughness Ra≥1μm, and drying to obtain the thick electrode.

[0005] The thick electrode prepared by the above scheme has the problems of poor cycle performance and poor storage performance, which limits its application in practice. Summary of the invention

[0006] The purpose of the present invention is to provide a thick negative electrode and a preparation method and application thereof. The present invention improves the flexibility of the negative electrode by compounding and using a dispersant and different types of binder compositions, solves the problems of poor electrolyte wettability of thick electrodes, long lithium ion migration paths, and large concentration polarization, improves kinetic properties, such as lithium precipitation, internal resistance, etc., improves the rate and low-temperature discharge performance of the battery, and ensures that the battery has good cycle performance. In lithium-ion battery electrodes, the binder provides adhesion between the electrode active material, the conductive agent, and the current collector, and maintains good contact between the active material and the conductive agent and the current collector, and between the active material and the active material. During the charge and discharge process, it can effectively maintain the integrity of the electrode structure, maintain a good electronic path and stable electrochemical properties, and ensure safe and effective operation of the battery.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In the first aspect, the present invention provides a negative thick electrode, which includes a current collector and a negative active material layer arranged on the surface of the current collector, the negative active material layer includes a negative active material, a conductive agent, a dispersant and a combined binder, the combined binder includes a binder A and a binder B, the binder A includes a block copolymer, the block copolymer has a polyacrylate segment in the middle, and includes polyacrylic acid segments and polyvinyl alcohol segments at both ends, and the binder B includes an emulsion-type binder.

[0009] In the negative thick electrode of the present invention, the binder A is a block copolymer binder, the middle of the block copolymer is a polyacrylate segment, and the two ends are polyacrylic acid (PAA) segments and polyvinyl alcohol (PVA) segments. Among them, the polyacrylate segment has a certain swelling ability for the electrolyte, forming an ion-conducting channel, which is beneficial to improve the wettability of the electrolyte in the thick electrode. The carboxyl group in the polyacrylic acid (PAA) segment and the hydroxyl group in the CMC form a three-dimensional network structure to inhibit electrode expansion. Among them, cross-linking is also generated between different binder A chains through condensation reactions. The condensation reaction occurs between the hydroxyl group of one chain and the carboxyl group of another chain. The condensation reaction further enhances the stability of the three-dimensional network structure.

[0010] Preferably, the monomer units of the binder B include any one or a combination of at least two of aromatic vinyl monomer units, aromatic conjugated diene monomer units, ethylenically unsaturated carboxylic acid monomer units, unsaturated carboxylic acid alkyl ester monomer units or acrylonitrile monomer units.

[0011] Preferably, the binder B comprises styrene-butadiene latex.

[0012] In the thick negative electrode of the present invention, the binder B is of emulsion type, and the negative electrode active material and the negative electrode active material are bonded to the current collector in a point-to-point manner. The binder B itself has good flexibility, and the binder A is a solution-type multi-polymer, which has rich functional groups in its molecular structure, and forms a mesh structure in the electrode in a face-to-face manner. On the one hand, the formed mesh structure has the benefit of improving the bonding force between the negative electrode active materials and between the negative electrode active materials and the current collector, and improving the pole piece peeling force of the thick electrode; on the other hand, the existence of the mesh structure also retains the channel for the insertion and extraction of lithium ions, but the binder A itself is brittle and poor in flexibility, and the pole piece active material is easy to fall off during the processing and charging and discharging of the pole piece. Therefore, the synergistic effect of the binder B and the binder A further improves the peeling force of the negative pole piece prepared by the above slurry and improves the flexibility of the pole piece. In addition, the use of binder A alone will form unstable carboxylates with the electrolyte and remain in the SEI film, forming an SEI film that cannot exist stably, which deteriorates the charge and discharge efficiency and cycle performance of the electrochemical device.

[0013] The thick negative electrode contains both binder A and binder B. The electrode sheet containing only binder A is hard and brittle, and has excellent dynamic performance. The use of binder A and binder B simultaneously makes the negative electrode sheet have good flexibility, which is conducive to processing, reduces the situation where active materials fall off from the electrode sheet, and reduces the risk of short circuit of the electrochemical energy storage device.

[0014] Preferably, the dispersant includes any one of sodium carboxymethyl cellulose, sodium carboxypropyl cellulose or sodium alginate, or a combination of at least two thereof.

[0015] Preferably, the negative electrode active material includes graphite.

[0016] Preferably, the conductive agent includes any one of conductive carbon black, graphene, carbon nanotubes or conductive fibers, or a combination of at least two thereof.

[0017] Preferably, the current collector comprises copper foil.

[0018] Preferably, based on the mass of the negative electrode active material layer being 100%, the mass fraction of the negative electrode active material is 91.8-98.9%, for example, 91.8%, 92%, 94%, 95% or 98.9%.

[0019] Preferably, the mass fraction of the dispersant is 0.1-2.2%, for example, 0.1%, 0.5%, 1%, 1.5% or 2.2%.

[0020] Preferably, the mass fraction of the binder A is 0.5-2.1%, for example, 0.5%, 0.8%, 1%, 1.5% or 2.1%.

[0021] Preferably, the mass fraction of the binder B is 0.1-1.7%, for example, 0.1%, 0.5%, 1%, 1.2% or 1.7%.

[0022] Preferably, the mass fraction of the conductive agent is 0.4-5%, for example, 0.4%, 1%, 2%, 3%, 4% or 5%.

[0023] In a second aspect, the present invention provides a method for preparing the thick negative electrode as described in the first aspect, the preparation method comprising the following steps:

[0024] (1) mixing a dispersant and a solvent to obtain a dispersant solution, mixing a negative electrode active material and a conductive agent to obtain a mixed material, and mixing the mixed material with the dispersant solution to obtain a mixed solution through primary dispersion;

[0025] (2) mixing part of the binder A with the mixed solution obtained in step (1) for secondary dispersion, adding a solvent and the remaining binder A for tertiary dispersion, adding the binder B, and stirring to obtain a negative electrode slurry;

[0026] (3) The negative electrode slurry is coated on the surface of the current collector, and the negative electrode thick electrode is obtained by drying, rolling and cutting.

[0027] In the preparation method of the present invention, a dispersant, a binder A and a binder B are added. The dispersant is added first so that it is evenly wrapped on the surface of the negative electrode active material, which is used to disperse the negative electrode active material on the one hand and helps to form a stable SEI film on the other hand; it avoids the problem of rapid capacity decay of the electrochemical energy storage device during the charge and discharge cycle when a single binder is used as both a binder and a dispersant.

[0028] Preferably, the solid content of the dispersant solution in step (1) is 1-2%, for example: 1%, 1.2%, 1.5%, 1.8% or 2%, etc.

[0029] Preferably, the degree of substitution of the dispersant is 0.5-1, for example, 0.5, 0.62, 0.71, 0.85 or 1.

[0030] Preferably, the part of binder A in step (2) accounts for 20-35% of the total mass of binder A, for example: 20%, 22%, 25%, 30% or 35%, etc.

[0031] Preferably, the thickness of the current collector in step (3) is 5 to 10 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0032] In a third aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the thick negative electrode as described in the first aspect.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The present invention improves the flexibility of the thick negative electrode by compounding and using dispersants and different types of binder compositions, solves the problems of poor electrolyte wettability of thick electrodes, long lithium ion migration paths, and large concentration polarization, improves kinetic properties such as lithium precipitation and internal resistance, and enhances the battery's rate and low-temperature discharge performance, while ensuring that the battery has good cycle performance. In lithium-ion battery electrodes, the binder provides adhesion between the electrode active material, the conductive agent, and the current collector, maintaining good contact between the active material and the conductive agent and the current collector, and between the active material and the active material. During the charge and discharge process, it can effectively maintain the integrity of the electrode structure, maintain a good electronic path and stable electrochemical properties, and ensure safe and effective operation of the battery.

[0035] (2) The battery made of the thick negative electrode of the present invention has a capacity retention rate of more than 90.1% after 3000 cycles of 1C / 1C at 25°C, a capacity retention rate of more than 89.42% after storage at 60°C for 30 days, a capacity recovery rate of more than 93.24% after storage at 60°C for 30 days, a 1C discharge rate of more than 93.10% at 25°C, and a 0.2C low-temperature discharge rate of more than 92.74% at 0°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic diagram of the binder described in Example 1 in the negative thick electrode.

[0037] Figure 2 It is a comparison chart of the cycle performance of the electrodes prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0039] Example 1

[0040] This embodiment provides a negative thick electrode, and the preparation method of the negative thick electrode is as follows:

[0041] (1) mixing sodium carboxymethyl cellulose and water to obtain a dispersant solution having a solid content of 1.5%, wherein the degree of substitution of the dispersant is 0.75, mixing graphite and conductive carbon black to obtain a mixture, mixing the mixture with the dispersant solution, and performing a primary dispersion to obtain a mixed solution;

[0042] (2) 32% of the binder A is mixed with the mixed solution obtained in step (1) for secondary dispersion, a solvent and the remaining 68% of the binder A are added for tertiary dispersion, a binder styrene-butadiene latex is added, and the mixture is stirred to obtain a negative electrode slurry;

[0043] (3) coating the negative electrode slurry on the surface of a copper foil with a thickness of 8.2 μm, drying, rolling, and cutting to obtain the negative thick electrode;

[0044] The mass ratio of graphite, conductive carbon black, sodium carboxymethyl cellulose, binder A and binder B in the negative thick electrode is 97.2:0.5:0.4:1.4:0.5;

[0045] The schematic diagram of the binder in the negative thick electrode is as follows Figure 1 shown.

[0046] Example 2

[0047] This embodiment provides a negative thick electrode, and the preparation method of the negative thick electrode is as follows:

[0048] (1) mixing sodium carboxymethyl cellulose and water to obtain a dispersant solution having a solid content of 1.5%, wherein the degree of substitution of the dispersant is 0.71, mixing graphite and conductive carbon black to obtain a mixture, mixing the mixture with the dispersant solution, and performing a primary dispersion to obtain a mixed solution;

[0049] (2) 30% of the binder A is mixed with the mixed solution obtained in step (1) for secondary dispersion, a solvent and the remaining 70% of the binder A are added for tertiary dispersion, a binder styrene-butadiene latex is added, and the mixture is stirred to obtain a negative electrode slurry;

[0050] (3) coating the negative electrode slurry on the surface of a copper foil with a thickness of 8 μm, drying, rolling, and cutting to obtain the negative thick electrode;

[0051] The mass ratio of graphite, conductive carbon black, sodium carboxymethyl cellulose, binder A and binder B in the negative thick electrode is 96.7:0.6:0.5:1.8:0.4.

[0052] Example 3

[0053] The only difference between this embodiment and the first embodiment is that the mass proportion of the binder A in the negative electrode active material layer is 0.3%, and the other conditions and parameters are exactly the same as those in the first embodiment.

[0054] Example 4

[0055] The only difference between this embodiment and the first embodiment is that the mass proportion of the binder A in the negative electrode active material layer is 2.4%, and the other conditions and parameters are exactly the same as those in the first embodiment.

[0056] Example 5

[0057] The only difference between this embodiment and the first embodiment is that the mass proportion of the binder B in the negative electrode active material layer is 0.05%, and the other conditions and parameters are exactly the same as those in the first embodiment.

[0058] Example 6

[0059] The only difference between this embodiment and embodiment 1 is that the mass proportion of the binder B in the negative electrode active material layer is 2%, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0060] Comparative Example 1

[0061] The only difference between this comparative example and Example 1 is that binder A is not added, and other conditions and parameters are exactly the same as those in Example 1.

[0062] Comparative Example 2

[0063] The only difference between this comparative example and Example 1 is that binder B is not added, and other conditions and parameters are exactly the same as those of Example 1.

[0064] Comparative Example 3

[0065] The only difference between this comparative example and Example 1 is that the binder A is replaced with acrylate, polyacrylic acid and polypropylene alcohol of equal mass, and the other conditions and parameters are exactly the same as those in Example 1.

[0066] Performance Testing:

[0067] A certain amount of binder polyvinylidene fluoride powder is added to N-methylpyrrolidone solvent, stirred and mixed evenly, and a glue solution with a solid content of 8% is prepared. The positive electrode active material lithium iron phosphate: carbon nanotube: conductive carbon black: polyvinylidene fluoride is added to the agitator in a mass ratio of 97.5%: 0.4%: 0.5%: 1.6%, and the positive electrode slurry is obtained after sufficient stirring. The prepared slurry is coated on the current collector. The thickness of the current collector carbon-coated aluminum foil is 16μm. Subsequently, it is dried in an oven, rolled, and cut into pieces to form a positive electrode sheet for preparing a battery. The negative thick electrode obtained in Examples 1-6 and Comparative Examples 1-3 is used as the negative electrode, a polyethylene (PE) porous polymer film is used as the isolation membrane, and 1.00mol / L LiPF6 / (DEC+EMC+EC) is used as the electrolyte to prepare a soft-pack lithium-ion battery. The performance of the lithium-ion battery is tested, and the test results are shown in Table 1:

[0068] Table 1

[0069]

[0070]

[0071] As can be seen from Table 1, from Examples 1-2, the battery made of the negative thick electrode of the present invention can achieve a capacity retention rate of more than 90.1% after 3000 cycles of 1C / 1C at 25°C, a capacity retention rate of more than 89.42% after storage at 60°C for 30 days, a capacity recovery rate of more than 93.24% after storage at 60°C for 30 days, a 1C discharge rate of more than 93.10% at 25°C, and a 0.2C low-temperature discharge rate of more than 92.74% at 0°C.

[0072] By comparing Example 1 and Examples 3-4, it can be seen that in the active material layer of the negative thick electrode of the present invention, the mass fraction of binder A will affect its performance. When the mass fraction of binder A is controlled at 0.5-2.1%, the performance of the obtained negative thick electrode is better. If the mass fraction of binder A is too small, the performance of the battery cell will not be significantly improved. If the mass fraction of binder A is too large, the negative electrode sheet will become brittle and hard, the active material will fall off severely during the processing, and the battery cell performance will deteriorate.

[0073] By comparing Example 1 and Examples 5-6, it can be seen that in the active material layer of the negative thick electrode of the present invention, the mass fraction of binder B will affect its performance. When the mass fraction of binder B is controlled at 0.1-1.7%, the performance of the obtained negative thick electrode is better. If the mass fraction of binder B is too small, the synergistic effect with adhesive A cannot be fully exerted, and the battery performance is poor. If the mass fraction of binder B is too large, the battery impedance becomes large and the low-temperature discharge performance of the battery becomes poor.

[0074] The cycle performance comparison of the electrode sheets described in Example 1 and Comparative Example 1 is shown in the figure Figure 2 As shown, by comparing Example 1 with Comparative Examples 1-2, it can be seen that the negative electrode sheet of the present invention contains both binder A and flexible binder B, and the electrode sheet containing binder A alone is hard and brittle, and has excellent dynamic performance. The simultaneous use of binder A and binder B makes the negative electrode sheet have good flexibility, which is conducive to processing, reduces the situation where active materials fall off from the sheet, and reduces the risk of short circuit of the electrochemical energy storage device.

[0075] By comparing Example 1 and Comparative Example 3, it can be seen that in the thick negative electrode of the present invention, the binder A is a block copolymer binder, the middle of the block copolymer is a polyacrylate segment, and the two ends are polyacrylic acid (PAA) segments and polyvinyl alcohol (PVA) segments. Among them, the polyacrylate segment has a certain swelling ability for the electrolyte, forming an ion-conducting channel, which is beneficial to improve the wettability of the electrolyte in the thick electrode. The carboxyl group in the polyacrylic acid (PAA) segment and the hydroxyl group in the CMC form a three-dimensional network structure to inhibit electrode expansion. Among them, cross-linking is also produced between different binder A chains through condensation reaction. The condensation reaction occurs between the hydroxyl group of one chain and the carboxyl group of another chain. The condensation reaction further enhances the stability of the three-dimensional network structure.

[0076] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A thick negative electrode, characterized in that: The negative thick electrode comprises a current collector and a negative active material layer disposed on the surface of the current collector, the negative active material layer comprises a negative active material, a conductive agent, a dispersant and a combined binder, the combined binder comprises a binder A and a binder B, the binder A is a block copolymer, the middle of the block copolymer is a polyacrylate segment, and both ends include a polyacrylic acid segment and a polyvinyl alcohol segment, and the binder B comprises an emulsion type binder; The binder B is styrene-butadiene latex; Based on the mass of the negative electrode active material layer being 100%, the mass fraction of the binder A is 0.5-2.1%; the mass fraction of the binder B is 0.1-1.7%.

2. The thick negative electrode according to claim 1, characterized in that: The monomer units of the binder B include any one or a combination of at least two of aromatic vinyl monomer units, aromatic conjugated diene monomer units, ethylenically unsaturated carboxylic acid monomer units, unsaturated carboxylic acid alkyl ester monomer units or acrylonitrile monomer units.

3. The thick negative electrode according to claim 1, characterized in that: The dispersant includes any one of sodium carboxymethyl cellulose, sodium carboxypropyl cellulose or sodium alginate, or a combination of at least two of them.

4. The thick negative electrode according to claim 1, characterized in that: The negative electrode active material includes graphite.

5. The thick negative electrode according to claim 1, characterized in that: The conductive agent includes any one of conductive carbon black, graphene, carbon nanotubes or conductive fibers, or a combination of at least two of them.

6. The thick negative electrode according to claim 1, characterized in that: The current collector includes copper foil.

7. The thick negative electrode according to claim 1, characterized in that: Taking the mass of the negative electrode active material layer as 100%, the mass fraction of the negative electrode active material is 91.8-98.9%.

8. The thick negative electrode according to claim 1, characterized in that: Based on the mass of the negative electrode active material layer being 100%, the mass fraction of the dispersant is 0.1-2.2%.

9. The thick negative electrode according to claim 1, characterized in that: Based on the mass of the negative electrode active material layer being 100%, the mass fraction of the conductive agent is 0.4-5%.

10. A method for preparing a thick negative electrode according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: (1) mixing a dispersant and a solvent to obtain a dispersant solution, mixing a negative electrode active material and a conductive agent to obtain a mixed material, and mixing the mixed material with the dispersant solution to obtain a mixed solution through primary dispersion; (2) mixing part of the binder A with the mixed solution obtained in step (1) for secondary dispersion, adding a solvent and the remaining binder A for tertiary dispersion, adding the binder B, and stirring to obtain a negative electrode slurry; (3) The negative electrode slurry is coated on the surface of the current collector, and the negative electrode thick electrode is obtained by drying, rolling and cutting.

11. The preparation method according to claim 10, characterized in that: The solid content of the dispersant solution in step (1) is 1-2%.

12. The preparation method according to claim 10, characterized in that: The degree of substitution of the dispersant is 0.5-1.

13. The preparation method according to claim 10, characterized in that: The part of binder A described in step (2) accounts for 20-35% of the total mass of binder A.

14. The preparation method according to claim 10, characterized in that: The thickness of the current collector in step (3) is 5-10 μm.

15. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative thick electrode according to any one of claims 1 to 9.